Gallosilicate glass and fiber for radiation detection. Issue 6 (22nd February 2023) - Tang, Manyun; Ma, Yan; Wen, Shaofei; Du, Guanxin; Chen, Jingfei; Li, Xueliang; Lv, Shichao; Zhou, Shifeng
Abstract: As ionizing radiation can cause harmful effects to human and electronic devices, accurate dose monitoring plays an important role in fields such as radiotherapy, nuclear industry, and aerospace. Currently, it is still a challenge to fabricate a miniaturized dosimeter that can achieve real‐time monitoring. Here, a gallosilicate glass with potential application in visualization detection of ultraviolet and ionizing radiation, as well as cumulative dose measurement, is presented. Color centers are induced in the glass upon exposure to ultraviolet or ionizing radiation, resulting in a darkening effect. The color change of glass is related to the energy and intensity of incident photons and can be erased by subsequent heat treatment. Electron paramagnetic resonance measurement indicates that the formation of color centers is associated with non‐bridging oxygen hole centers related to gallium. The glass can be fabricated into fiber with perfect core‐cladding structure, which provides an alternative for preparing a new type of high‐sensitivity radiation dosimeter.